(untitled) (Archives of Pediatrics of Uruguay, 2025)
Vascular lesions are a group of entities that are sometimes confused in terms of definitions and terminology. It is common that healthcare teams may use inconsistent nomenclature when referring to these lesions, which can lead to misinterpretations. In this paper, we aim to unify concepts based on the existing classification of vascular lesions by the International Society for the Study of Vascular Anomalies (ISSVA). This classification divides them into two main groups: vascular tumors (abnormal cellular proliferation) and vascular malformations (abnormalities in vascular endothelial architecture). We describe the characteristics of venous malformations, capillary malformations, lymphatic malformations, and arteriovenous malformations. These conditions differ in their clinical, imaging, histological, prognostic, and therapeutic features. Management can be simple or complex and must be tailored to each patient. Therefore, these conditions are ideally approached by a multidisciplinary team. This team should include a pediatric surgeon, vascular surgeon, interventional radiologist, dermatologist, plastic surgeon, among other specialists who are knowledgeable about these pathologies and have appropriate management strategies.